2014
DOI: 10.1016/j.drugalcdep.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of injecting behavior in the Amsterdam Cohort Study among drug users

Abstract: Background:Injecting frequency among people who inject drugs (IDU) can change along distinct trajectories, which can reflect on incidence of HIV and HCV infections. We aimed at assessing these patterns of longitudinal changes, their predictors and their association with the incidence of HIV and HCV. Methods:We analyzed data from the Amsterdam Cohort Study among Drug Users, selecting participants recruited 1985-2005, injecting drugs before cohort entry and with records in at least three different six months int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(39 reference statements)
2
7
1
Order By: Relevance
“…Even with this classification uncertainty, summarizing 20 years' follow‐up data at individual level in relation to several injection drug use trajectories has proven useful. Further, the primary findings were consistent with studies from other settings . Several factors were found to be predictive of these trajectory classes, which further indicate that the identified trajectory classes were different from each other.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Even with this classification uncertainty, summarizing 20 years' follow‐up data at individual level in relation to several injection drug use trajectories has proven useful. Further, the primary findings were consistent with studies from other settings . Several factors were found to be predictive of these trajectory classes, which further indicate that the identified trajectory classes were different from each other.…”
Section: Discussionsupporting
confidence: 84%
“…However, only daily heroin injection remained positively associated with being in the ‘persistent injection' and ‘gradual cessation' groups in the multivariable model. Studies have shown that polydrug use is associated with change in injecting behavior . In the current study, speedball injection was only marginally associated with ‘persistent injection' in bivariable analyses, which provided limited information to help differentiate long‐term drug use trajectories.…”
Section: Discussioncontrasting
confidence: 58%
“…This method is used to identify relatively homogeneous clusters of trajectories of stability or change over time in the presence of repeated observations [23,24]. For each behavioral outcome, the number of groups and their shape were informed by previous studies examining drug use trajectories [25,26] and several statistical criteria [23,24]. We considered models with up to 4 and 5 groups for binary and count outcomes, respectively.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Among people who inject drugs more broadly, Genberg and colleagues identified five patterns of use in a 20‐year study of 1716 participants (87% heroin users): ‘early cessation’ (19%), ‘delayed cessation’ (16%), ‘late cessation’ (18%), ‘frequent relapse’ (16%) and ‘persistent injection’ (32%). Similarly, Mikolajczyk and colleagues identified five patterns of injecting among 740 people who inject drugs over 4.5–5.5 years: ‘rare to no injecting’ (23%), ‘constant daily or several times daily injecting’ (15%), ‘variable injecting’ (19%), ‘every 2nd day and less frequent injecting’ (32%) and ‘decrease in injecting’ (12%).…”
Section: Introductionmentioning
confidence: 99%